The modern face of newborn screening - Yin-Hsiu Chien; Wuh-Liang Hwu (Pediatrics and Neonatology)
Newborn screening (NBS) has been developed for years to identify newborns with severe but treatable conditions. Taiwan's NBS system, after the initial setup for a total coverage of newborns in 1990s, was later optimized to ensure the timely return of results in infants with abnormal results. Advancements in techniques such as Tandem mass spectrometry enable the screening into a multiplex format and increase the conditions to be screened. Furthermore, advances in therapies, such as enzyme replacement therapy, stem cell transplantation, and gene therapy, significantly expand the needs for newborn screening. Advances in genomics and biomarkers discovery improve the test accuracy with the assistance of second-tier tests, and have the potential to be the first-tier test in the future. Therefore, challenge of NBS now is the knowledge gap, including the evidence of the long-term clinical benefits in large cohorts especially in conditions with new therapies, phenotypic variations and the corresponding management of some screened diseases, and cost-effectiveness of extended NBS programs. A short-term and a long-term follow-up program should be implemented to gather those outcomes better especially in the genomic era. Ethical and psychosocial issues are also potentially encountered frequently. Essential education and better informed consent should be considered fundamental to parallel those new tests into future NBS.